The Role of Educational Technology in Ensuring Access to Quality Learning within the Education System - Khoirul Anwar; Moch. Karim Amirudin; Muhammad Hadziq ‘Aqil; Nur Anim Jauhariyyah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze the role of educational technology in ensuring access to quality learning at Darussalam Senior High School, Blokagung, Banyuwangi. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation. The findings indicate that educational technology enhances the effectiveness, flexibility, and inclusivity of learning, although challenges remain in terms of infrastructure, digital literacy, and limited access to devices. Optimization efforts through improving facilities and strengthening teacher competencies are necessary to ensure that technology can optimally support equity and quality in learning. Keywords : Educational Technology, Quality Learning, Education System